(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Crime scene serves as the starting point for forensic science and can generate valuable data that must be meticulously, methodically, scientifically, and lawfully gathered. If the crime scene is not handled appropriately, it can become misleading and render crucial information useless, leading to an investigation on the wrong path. Forensic science has undergone a revolution thanks to the use of DNA technologies. Many times, due to the investigator’s lack of scientific expertise regarding the proper collection, preservation, storage, and transportation of biological evidence, the investigator is unable to acquire accurate DNA analysis results, which reduces the value of the evidence in court. Purity, quantity, and rate of DNA degradation are just a few of the many variables that go into creating a decent DNA profile from a biological sample. We highlight and provide useful strategies and recommendations to assist medical, forensic, and law enforcement professionals in handling biological evidences for DNA analysis to prevent contamination, deterioration, and loss of biological evidence’s value.